The development of contemporary linguistics and its relevance to law - Cárcova, Carlos María (2021)
This text aims to offer legal operators a synthetic tour of the development of linguistics. The objective is to provide a fundamental tool for the elucidation of theoretical problems of Law, taking into account its linguistic and semiotic aspect.